Trends in fatalities from road traffic injuries and associated factors of patients admitted to the emergency department of St. Luke Hospital, South West Shewa Zone, Ethiopia - Beyera, Teshale Merga; Serbessa, Sheleme Duga; Fetensa, Getahun; Woldemichael, Kifle (Frontiers in Disaster and Emergency Medicine, 2024)
Introduction Road traffic injuries are a major global public health problem. They are fatal or non-fatal injuries resulting from a road traffic accident involving at least one moving vehicle on a path or road open to public traffic. Therefore, this study aimed to determine the trends in fatalities from road traffic injuries and the associated factors of patients admitted to the emergency department of St. Luke Hospital. Methods An institution-based cross-sectional study was conducted from July 10 to 30, 2019. The study on the trends in road traffic injuries was conducted monthly bases from January 1 to December 31, 2018. A total of 364 road traffic–injured victim records were included. A simple random sampling technique was used for the record selection. A structured data abstraction format was used to gather the required data. Binary logistic regression and multivariate logistic regression were used to determine the association between the outcome and explanatory variables. Adjusted odds ratios (AORs) at 95% confidence intervals were used to report independent variables. Results and conclusions The average annual fatalities from road traffic injuries was 8.34% deaths/month. The magnitude of road traffic injury fatalities was 8.79%. Of all victims who visited the hospital, 75.5% were male. The median age of the victims was 26 (51.6%), with a range from 6 to 70. The identified risk factors for road traffic injury fatalities were a lack of ambulance for transportation to the hospital after the accident (AOR = 7.093, 95% CI [1.950, 25.793], p = 0.003) and head injury (AOR = 2.515, 95% CI [1.075, 5.885], p = 0.034). Road traffic injury fatalities are an important public health problem that needs special attention. A shortage of ambulance service for transportation and injury sites related to head injury were associated factors. So it is important to establish and strengthen advanced prehospital care and an effective ambulance system for transporting victims with road traffic injuries.